2017
DOI: 10.1088/1742-6596/891/1/012202
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of liquid-jet high-pressure booster compressors

Abstract: Abstract. There are almost no experimental data on the head-capacity curves for liquid-jet compressors with the inlet gas pressure of liquid-jet apparatus more than 1 MPa. Meanwhile, this range is important for many engineering applications in which relatively low compressor ratio is required for the pumping of gas under high pressure. This is mostly the case when gas circulation is to be provided in a closed or almost closed circuit. A head-capacity curve of a liquid-jet apparatus has been estimated experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Gas enters through the inlet (8), passes through the inlet pipe (9) and the float flowmeter (10), and is controlled by the inlet valve (11). The gas is mixed with the working fluid in the pressure-stabilizing tank (12), and the mixed liquid is passed through the diffuser pipe (7) before being discharged back into the water tank for recycling. Based on the design diagram of the pump system experimental platform, the experimental setup of the system was constructed, as shown in Figure 2.…”
Section: Experimental Setup and Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas enters through the inlet (8), passes through the inlet pipe (9) and the float flowmeter (10), and is controlled by the inlet valve (11). The gas is mixed with the working fluid in the pressure-stabilizing tank (12), and the mixed liquid is passed through the diffuser pipe (7) before being discharged back into the water tank for recycling. Based on the design diagram of the pump system experimental platform, the experimental setup of the system was constructed, as shown in Figure 2.…”
Section: Experimental Setup and Instrumentsmentioning
confidence: 99%
“…Eisallak [12] conducted experimental analysis of the impact of inlet pressure on jet streams. The results showed that when the inlet pressure is relatively weak, the performance of the liquid-gas jet pump improves, while with higher inlet pressure, the pump's efficiency decreases.…”
Section: Introductionmentioning
confidence: 99%